Examining the proposed instrument model in learning management system use: a pilot study - Zulherman, Zulherman; Supriansyah, Supriansyah; Bandarsyah, Desvian; Shahul Hamid, Mohamed Nazreen (Intelektual Pustaka Media Utama, 2025)
Online and distance learning technology with the learning management system (LMS) is an example of the application of online learning models at universities, which is the impact of technological developments. However, advances in LMS technology still need to be implemented in universities, the problem of university readiness being the main factor. Another area for improvement is the level of computer self-efficacy (CSE) among LMS users. Therefore, before the actual research was carried out, instrument testing was carried out regarding the factors influencing LMS users at the university. After testing the limited instrument on 63 university students, the results showed that of the six constructs with 21 indicator items, it was proven that only one indicator item was invalid. However, the reliability test has met the criteria. The conclusion of the initial test results of the instrument was declared valid and reliable, so it was suitable for actual testing.